EKONOMI KREATIF SEBAGAI PELUANG REMAJA AUTISTIK BERWIRAUSAHA - Chrisdina; Jefri Audi Wempi; Nurul Hidayah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2020)
Abstract The existence of autistic individuals in Indonesia continues to increase, this can be seen from the number of inclusive schools that continue to emerge. The increase in the number of schools provides wider opportunities to have abilities both academically and skills. The academic ability achieved has not been able to allow autistic adolescents to have a job. Apart from that, parents also need to get an understanding of how to make an effort that these autistic adolescents can do. The creative economy, especially crafts, can be a solution to these problems. The LSPR Communication and Business Institute sees this phenomenon as an opportunity to be able to develop an empowerment program for autistic adolescents so that they can have the opportunity to be able to earn their own income. Through the work training center program, autistic adolescents are taught the skills to process textiles using dyeing techniques. During the Covid 19 pandemic the learning system applied was online. The advantage of online training allows parents to assist and be able to ask questions from the process to the opportunity to market the product. After the program has been running for 6 months, 2 home businesses have been formed, which have been carried out by autistic teenagers and their parents. It was concluded that the empowerment program for adolescents with autism must be accompanied by building awareness and the communication is well accepted. ability of parents to become entrepreneurs. The use of google meet as a new technology in Keywords: autism youth; creative economy; entrepreneurship Abstrak Keberadaan individu autis di Indonesia terus bertambah, ini nampak dari jumlah sekolah inklusi yang terus bermunculan. Pertambahan jumlah sekolah memberikan peluang yang lebih luas untuk memiliki kemampuan baik secara akademik maupun keterampilan. Kemampuan akademik yang dicapai belum dapat memberikan kesempatan para remaja autis memiliki pekerjaan. Selain hal itu orangtua juga perlu mendapat pemahaman bagaimana membuat sebuah usaha yang mampu dilakukan oleh para remaja autis tersebut. Ekonomi kreatif khususnya kerjainan dapat menjadi salah satu pemecahan masalah tersebut. Institut Komunikasi dan Bisnis LSPR melihat fenomena tersebut menjadi sebuah peluang untuk dapat mengembangkan sebuah program pemberdayaa remaja autis agar mampu memiliki peluang untuk dapat memiliki penghasilan sendiri. Melalui program balai latihan kerja para remaja autis diajari keterampilan mengolah teksil dengan teknik celup. Pada masa pandemi Covid 19 sistem pembelajaran yang diterapkan adalah melalui daring. Keuntungan pelatihan daring memberikan kesempatan orangtua untuk mendampingi dan dapat bertanya mulai dari proses hingga kesempatan untuk memasarkan produk. Setelah program berjalan 6 bulan sudah terbentuk 2 usaha rumahan yang dikerjakan oleh remaja autis dan orangtuanya. Disimpulkan bahwa program pemberdayaan reamja autis harus dibarengi dengan dibangunnya kesadaran dan kemampuan orangtua untuk berwirausaha. Penggunaan media google meet sebagai teknologi baru dalam berkomunikasi dapat diterima dengan baik.